2019
DOI: 10.1093/aobpla/plz063
|View full text |Cite
|
Sign up to set email alerts
|

Stem and leaf growth rates define the leaf size vs. number trade-off

Abstract: The trade-off between leaf number and individual leaf size on current-year shoots (twigs) is crucial to light interception and thus net carbon gain. However, a theoretical basis for understanding this trade-off remains elusive. Here, we argue that this trade-off emerges directly from the relationship between annual growth in leaf and stem mass, a hypothesis that predicts that maximum individual leaf size (i.e. leaf mass, Mmax, or leaf area, Amax) will scale negatively and isometrically with leafing intensity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…Stem elongation (cm) and the number of leaves per plant were measured for each plant at the beginning of stress (H i , L i ), at 30 days (H 30 , L 30 ) and at 60 days (H 60 , L 60 ) of drought. Stem growth rate (SGR) and leaf production rate (LPR) were estimated from these parameters according to the equations described by Sun et al (2019) and Rodrigues de Lima et al 2019.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Stem elongation (cm) and the number of leaves per plant were measured for each plant at the beginning of stress (H i , L i ), at 30 days (H 30 , L 30 ) and at 60 days (H 60 , L 60 ) of drought. Stem growth rate (SGR) and leaf production rate (LPR) were estimated from these parameters according to the equations described by Sun et al (2019) and Rodrigues de Lima et al 2019.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Previously, Dombroskie and Aarssen (2012) found a leaf size-leafing intensity trade-off at the plant level in 16 broadleaf tree species in Canada. Similarly, Sun et al (2019) found a diminishing return between leaf size and leafing intensity in bamboo species.…”
Section: Discussionmentioning
confidence: 82%
“…The dominant species (e.g., Rhododendron simiarum , Schima superba , Cyclobalanopsis glauca , Symplocos sumuntia , Cyclobalanopsis multinervis , Tsuga chinensis , Taxus wallichiana , Acer elegantulum , Illicium angustisepalum ) and site characteristics of the Wuyishan National Nature Reserve were listed in Sun et al. (2019a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the leaf–stem growth hypothesis showed that the scaling for the trade‐off between individual leaf mass and leafing intensity is governed by – α , where α is the exponents of total leaf mass versus stem mass (Sun et al., 2019a). Therefore, the isometric trade‐off in leaf size/number may deduce from the tightly isometric relationship between leaf and stem (Yang et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation